The biofouling of reverse osmosis membranes: From characterisation to control. - Lydia Charlotte Powell (2011)
Membrane technology can be utilised for the high purification and desalination of water. However membrane filtration processes are commonly impeded by membrane fouling, which can lead to flux decline and an overall reduction in separation efficiency within the process. Therefore the aim of this research study was a comprehensive investigation of the issue of biofouling on industrial RO membranes through molecular biology techniques, characterisation of surface charge of foulant bacteria and RO membrane surface and AFM imaging and force measurements on clean and fouled membranes for the determination of adhesion force and micromechanical properties. The laboratories within Gwangju Institute of Science and Technology, South Korea and Swansea University, Wales were equipped for the scope of this research work. Research focused on the extraction of microbial DNA obtained from fouling layers on the surface of Reverse Osmosis Membranes obtained from the Fujairah Water and Power Plant, UAE. The use of the culture independent method of the molecular technique based on the 16S rDNA sequence and constructed gene libraries, was then used to determine the bacterial species that caused significant fouling on the RO membrane. Four bacterial species isolated from the fouling layer from the RO membrane were characterised in terms of electrophoretic mobility and zeta potential to determine the cell surface charge within various industrial relevant environments for the elucidation of cell adhesion mechanisms to the membrane surface. AFM images of virgin and fouled membranes were obtained and analysed to reveal the roughness of the surface which could influence fouling and the surface charge of the membranes were measured through the method of streaming potential at various industrial relevant environments to further elucidate the mechanisms of cell adhesion to the membrane surface. Force measurements were performed to reveal the adhesion force and elasticity values of virgin, process fouled and purposely fouled with the four bacterial isolates, to determine process behaviour in various environmental conditions. Through this research and future work, it is hoped that a rational strategy for economic and effective cleaning processes will be developed which will maintain efficient membrane operation and prolong membrane life, thus enabling the reduction of operating costs of such processes.